A new electronic device for measuring pulse and oxygen concentration - Myint, Cho Zin (Curtin University, 2011)
Sensor devices such as pulse oximetry are practical tools used by most healthcare professionals, and even patients. An electronic sensor device that has the capability to measure physiological signs of saturation of arterial oxygen (SpO2) and heart beat rate of the human body has been developed in this study.The hardware design of the sensor device consists of a microcontroller PIC18F452, an external flash memory, and a transceiver unit. The most suitable sensors of red and infra red LEDs are installed on the arms of the plastic clip and functioned with the right resistor values. The red and infra red lights are detected by the photo diode and converted to digital numbers by the Assembly Language software program embedded into the microcontroller PIC18LF452. Those digital numbers are converted to SpO2 value in percentage level. A low power dual operational amplifier LM358 is used to amplify the current signal of the two lights, which depends on the intensity and visibility of the two lights. The output signals are displayed in 16 characters and 2 lines on Hitachi HD44870 compatible liquid crystal display (LCD). In order to display this data on personal computer (PC) monitor, the data is also transmitted via Universal Synchronous Asynchronous Receiver Transmitter (USART) ports of microcontroller to a PC. A Visual Basic 6 programming language is installed in the PC to display the wave forms, the percentage of the SpO2 level, and the pulse rate.Pulse oximetry has a promising future in the healthcare industry. This research enables a more efficient and economical means for managing the healthcare of the growing population.